Study of the In Vitro Digestion of Olive Oil Enriched or Not with Antioxidant Phenolic Compounds. Relationships between Bioaccessibility of Main Components of Different Oils and Their Composition - Jon Alberdi-Cedeño; María L. Ibargoitia; María D. Guillén (MDPI AG, 2020)
The changes provoked by in vitro digestion in the lipids of olive oil enriched or not with different phenolic compounds were studied by proton nuclear magnetic resonance (1H NMR) and solid phase microextraction followed by gas chromatography/mass spectrometry (SPME-GC/MS). These changes were compared with those provoked in the lipids of corn oil and of virgin flaxseed oil submitted to the same digestive conditions. Lipolysis and oxidation were the two reactions under consideration. The bioaccessibility of main and minor components of olive oil, of phenolic compounds added, and of compounds formed as consequence of the oxidation, if any, were matters of attention. Enrichment of olive oil with antioxidant phenolic compounds does not affect the extent of lipolysis, but reduces the oxidation degree to minimum values or avoids it almost entirely. The in vitro bioaccessibility of nutritional and bioactive compounds was greater in the olive oil digestate than in those of other oils, whereas that of compounds formed in oxidation was minimal, if any. Very close quantitative relationships were found between the composition of the oils in main components and their in vitro bioaccessibility. These relationships, some of which have predictive value, can help to design lipid diets for different nutritional purposes.